Effectiveness of acupuncture treatment of women with menopausal syndrome applying and not applying hormonal replacement therapy (Menopause Review/Przegląd Menopauzalny, 2011)

(untitled) - Woźniak, Piotr; Ziółkowska, Ewa; Stetkiewicz, Tomasz; Oszukowski, Przemysław
Background : Migraine because of a high morbidity rate generates high expenses for the health-care system and also for the patients. It triggers decrease of life comfort and frequently obstructs normal functioning. All authors of studies pay attention to definite higher incidence in women. Not in all patients is pharmacotherapy effective; some of them decide on acupuncture exams. Simultaneously women between 48 and 52 years of life suffer from menopause. Some of them decide to take hormonal replacement therapy. Aim of the study : In the research we retrospectively subjected to evaluation the effect of therapeutic acupuncture exams carried out because of occurrence of migraine in a group of women in menopausal stage, in two groups: applying and not applying hormonal replacement therapy Materials and methods : Medical examination survey of 48 patients aged 49-55 with migraine not responding to pharmacological treatment; 25 of them administer transdermal hormonal replacement therapy. All of patients undergo a whole cycle of 10 acupuncture treatments. Patients before the first exam and after the whole cycle answered the question in the questionnaire elaborated for the needs of this research. Furthermore, under usage of acupuncture treatment patients rate its analgesic effectiveness with a ten-point scale. Results : In the group of patients applying HTZ pain ailments regression was faster. Conclusion : Acupuncture is a safe method and recommended in treating migraine. Usage of HTZ in patients positively influences results of acupuncture therapy.